2021
DOI: 10.21203/rs.3.rs-388641/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differentiating Brucella Spondylitis from Tuberculous Spondylitis by the Conventional MRI and MR T2 Mapping: A Prospective Study

Abstract: Background Brucellar spondylitis (BS) and tuberculous spondylitis (TS) which cause initial bacteremia and show granulomatous lesions are the two leading types of spinal inflammatory. BS is easy to miss or maybe misdiagnosed as TS. Our purpose differentiates brucella spondylitis (BS) from tuberculous spondylitis (TS) in conventional MR imaging and MR T2 mapping.Methods We performed on 26 BS and 27 TS patients in conventional MR imaging and MR T2 mapping. We analyzed the features in conventional MR imaging and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Previous studies have demonstrated that paravertebral abscess, severe bone destruction, and intervertebral disc height loss were suggestive of TS, while local bone damage and confined paravertebral involvements were suggestive of BS, which can be proved by our results (57). In addition to that, endplate sclerosis and osteophytes are more common in BS than in TS, while disc height loss is more frequent in TS, which is in agreement with previous studies (37,58,59).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have demonstrated that paravertebral abscess, severe bone destruction, and intervertebral disc height loss were suggestive of TS, while local bone damage and confined paravertebral involvements were suggestive of BS, which can be proved by our results (57). In addition to that, endplate sclerosis and osteophytes are more common in BS than in TS, while disc height loss is more frequent in TS, which is in agreement with previous studies (37,58,59).…”
Section: Discussionsupporting
confidence: 92%